Battle in the skies : budget airlines in Singapore - Cai, Serene Xinchun (2008)
The aim of this research is to explore the competition between budget airlines in Asia from a consumer's perspective. In addition, the study also hoped to identify and recommend innovative areas a budget airline can focus on to compete effectively.